Human Capital Theory: Intersecting Educational and Economic Theories - Paul Bouchard (Adult Education Research Conference, 2008)
Training policy in the developed world is increasingly influenced by the perception that the future lies in developing the Knowledge Economy through investments in “Human Capital”. There are some problems with this simplistic view of contemporary economics.
Keywords: human capital; knowledge economy; training policy